Design and Research of Thrust Bearing for Datengxia Hydro-generator - GE Liangcheng; FAN Xiaofu; LUO Haiqiang; WU Zhongde; LIU Pingan (Renmin Zhujiang)
The design of thrust bearing of Datengxia hydro generator and the improvement measures of cooling system are introduced. The design of thrust bearing of large hydro generator focuses on the support structure, parameters and cooling method. Thrust tile and support structure are the basis to ensure the performance of thrust bearing, while lubrication and cooling have an important influence on the performance of thrust bearing. For the large hydro generator with low speed and heavy load, the spherical pillar bearing with small pillar and double-layer tile thrust bearing is one of the best choices. The thrust bearing is cooled by internal circulation, and the circulation of oil in the oil tank is carried out according to the set path in order to ensure the cooling efficiency and achieve the designed cooling effect. The oil baffle plate (oil scraping brush) reduces the influence of hot oil carried by the mirror plate on the tile temperature, as well as the effective separation of hot and cold oil, which is conducive to reducing the oil inlet temperature of the tile, and thus reducing the tile temperature.